2015
DOI: 10.1682/jrrd.2014.04.0109
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of lower-limb muscle power training to enhance locomotor function poststroke

Abstract: Abstract-Poststroke motor control is characterized by greatly reduced muscle power generation. To date, the extent to which muscle power limits walking performance or whether its remediation should be a primary component of locomotor rehabilitation has yet to be established. The purpose of this study was to examine the feasibility and the effects of Poststroke Optimization of Walking using Explosive Resistance training, an intervention aimed at improving poststroke muscular and locomotor function. Twelve subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Four of the included studies utilized a strength training intervention through power training, 26 by comparing eccentric and concentric resistance training, 29,44 or strength training exercises. 34 The change in gait speed effect sizes range from 0.4 to 0.67.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the included studies utilized a strength training intervention through power training, 26 by comparing eccentric and concentric resistance training, 29,44 or strength training exercises. 34 The change in gait speed effect sizes range from 0.4 to 0.67.…”
Section: Resultsmentioning
confidence: 99%
“…34 The majority of rehabilitation research has focused on traditional resistance training in individuals post-stroke, 22,3537 with only one other study focusing on power training. 21,38 Therefore, it is difficult to compare our results to previous studies, however comparisons have been made to higher intensity resistance training programs and the one study found that focuses on the time component needed for proper power training.…”
Section: Discussionmentioning
confidence: 95%
“…This criterion was used because differences in lower limb maximal velocity occur at relatively low external forces and are most closely associated with gait velocity in older individuals. 21,29 Peak isotonic paretic (PKP) and non-paretic knee power (NPKP) were normalized to bodyweight (kg) for data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations